Effects of 3‐hydroxyflavone on the cellular and molecular characteristics of bovine embryos produced by somatic‐cell nuclear transfer. Issue 3 (10th January 2014) - Su, Jianmin; Wang, Yongsheng; Li, Wenzhe; Gao, Mingqing; Ma, Yefei; Hua, Song; Quan, Fusheng; Zhang, Yong
SUMMARY This study aimed to investigate the effects of 3‐hydroxyflavone, a natural antioxidant pigment enriched in vegetables, on the developmental cellular and molecular characteristics of bovine somatic‐cell nuclear transfer (SCNT) embryos. There were no significant differences in the cleavage rate at 48 hr of culture or in the inner cell mass (ICM)‐to‐trophectoderm (TE) ratio between 3‐hydroxyflavone addition and untreated (control) groups (P > 0.05). 3‐hydroxyflavone (20 µM) did, however, increase the cleavage rate at 24 hr of culture and the blastocyst‐formation rate on Days 6 and 7 (P < 0.05); decrease the levels of intracellular reactive oxygen species in two‐, four‐, and eight‐cell stage embryos (P < 0.05); increase H3K9ac levels in two‐ and four‐cell stages (P < 0.05); increase the total cell number; and decrease the apoptosis index in Day‐7 blastocysts. Furthermore, the addition of 3‐hydroxyflavone resulted in lower expression of the stress‐related gene HSP70.1 and pro‐apoptotic gene BAX, as well as higher expression of the anti‐apoptotic gene BCL‐xL and pluripotency‐related genes OCT4 and SOX2 in Day‐7 blastocysts produced by SCNT (P < 0.05). The addition of 3‐hydroxyflavone during in vitro culture thus exerted beneficial effects on preimplantation development of bovine SCNT embryos both at the cellular and molecular levels. Mol. Reprod. Dev. 2014. © 2014 Wiley Periodicals, Inc.